2012
DOI: 10.1007/s10965-012-9916-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of CO2/CH4 separation characteristics of polyethersulfone by modifying with polydimethylsiloxane and nano-silica

Abstract: Porous asymmetric polyethersulfone (PES) hollow fiber membrane was fabricated via dry/wet spinning process. The spinning dope consisted of 18 wt.% PES in N-methyl-2-pyrrolidone (NMP) solvent. Distilled water was used as bore fluid to make hollow fiber membrane without inner skin layers. Then, a skin layer consisting of poly (4-vinyl pyridine), PVP, silicon rubber PDMS and silica nanoparticles (nanoSiO 2 ) was transferred to the PES substrate surface by means of a dip coating method, leading to a nanocomposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…It is helpful to predict the tear strength of the vulcanizates by examining their fractured surfaces . Usually, the more tear line in fractured surface, the more energy could be dissipated in a tear process and higher tear strength of the vulcanizates will be.…”
Section: Resultsmentioning
confidence: 99%
“…It is helpful to predict the tear strength of the vulcanizates by examining their fractured surfaces . Usually, the more tear line in fractured surface, the more energy could be dissipated in a tear process and higher tear strength of the vulcanizates will be.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the incorporation of silica nanoparticles in the membrane can lead to a higher CO 2 P and, consequently, a higher CO 2 /CH 4 selectivity . PES‐based mixed‐matrix membranes with the incorporation of different inorganic fillers have been studied by some authors . The blending of PES with other polymers is another approach that has been used to improve its gas‐permeation properties.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a hard rigid filler considerably decreased the impact strength as the filler that was dispersed in the polymer matrix acted as stress concentrator. Sharif et al 62 reported that the impact strength of the PA6/halloysite nanotube (HNT) nanocomposites blend increased up to 300% with the addition of 20 wt % ENR-50 as compared to that of the PA6/HNT nanocomposites alone. The ENR-50 could delay the crack propagation during notch Izod testing; this indicated that a high impact energy was needed for failure.…”
Section: Pa6/enr Blendsmentioning
confidence: 99%